Faktor-Faktor yang mempengaruhi ASI Eksklusif pada bayi usia 6-12 bulan di PMB Husniyati Palembang - Trifa Putri Sholeha; Fika Minata Wathan; Bina Aquari; Rizki Amalia (STIKes Budi Mulia Sriwijaya, 2025)
Exclusive breastfeeding is breastfeeding without additional food and drink for babies aged zero to six months. The objective of this study is to reveal the relationship of mother's knowledge, husband's support, and health workers’ support simultaneously with exclusive breastfeeding at PMB Husniyati Palembang in 2024. This is a quantitative study using an analytical survey method with a cross-sectional approach. The population of this study was all mothers who had babies aged 6-12 months old, totaling 100 respondents. The sample of this study was taken by using the Slovin formula resulting in 50 respondents chosen using accidental sampling techniques. Data were analyzed using the Chi Square test. The univariate analysis showed that 26 respondents (52.0%) did not provide exclusive breastfeeding, and 24 respondents (48.0%) provided exclusive breastfeeding. The results of bivariate analysis showed that there was relationship of mother's knowledge with the p-value of 0.022, husband's support with the p-value of 0.022, and health workers’ support with the p-value of 0.025 with exclusive breastfeeding. It can be concluded that there really is a relationship between mothers’ knowledge, husband's support, and health workers’ support with exclusive breastfeeding Keywords: Exclusive Breastfeeding